Early changes in estimated glomerular filtration rate post-initiation of empagliflozin in EMPEROR-Reduced - Zannad, Faiez; Ferreira, João Pedro; Gregson, John; Kraus, Bettina Johanna; Mattheus, Michaela; Hauske, Sibylle J.; Butler, Javed; Filippatos, Gerasimos; Wanner, Christoph; Anker, Stefan D.; Pocock, Stuart J.; Packer, Milton (European journal of heart failure, 2022)
Aims Sodium-glucose cotransporter 2 inhibitors (SGLT2i) may induce an early post-initiation decrease of estimated glomerular filtration rate (eGFR), which does not impact the SGLT2i benefits. The occurrence, characteristics, determinants, and clinical significance of an initial eGFR change among patients with heart failure with reduced ejection fraction require further study. In this study we aimed to describe eGFR change from randomization to week 4 (as percent of change relative to randomization) and assess its impact in EMPEROR-Reduced. Methods and results Landmark analyses (week 4) were performed. eGFR change was available in 3547 patients out of 3730 (95%). The tertiles of post-initiation % eGFR change for empagliflozin were: tertile 1 (T1) ≤−11.4%; T2 ≥−11.4% to ≤−1.0% and T3 ≥0.0%. The placebo group tertiles were: T1 ≤−6.5%; T2 ≥−6.4% to ≤+3.6%; and T3 ≥+3.6%. On average, empagliflozin induced a leftward distributional shift of initial eGFR changes of −2.5 ml/min/1.73 m2 versus placebo. In the empagliflozin group, after covariate adjustment, the risk of cardiovascular and renal outcomes did not differ between patients in whom early post-treatment initiation eGFR decreased (T1) and patients in whom it increased (T3). However, in the placebo group, patients in whom early post-treatment initiation eGFR decreased (T1) had a higher risk of sustained worsening kidney function and all-cause mortality compared to patients in whom eGFR increased (T3) (hazard ratio [HR] 2.38, 95% confidence interval [CI] 1.25-4.55 and HR 1.37, 95% CI 1.01-1.85, respectively). Conclusion A mild eGFR decrease may be expected after the initiation of empagliflozin, and it is not associated with untoward heart failure, mortality, or kidney safety events. Clinicians should not be concerned with early eGFR changes post-initiation of empagliflozin.